Figure 10 from: Fernandez-Triana J, Buffam J, Beaudin M, Davis H, Fernandez-Galliano A, Griffin E, Lin S-Y, McAulay MK, Richter R, Rodriguez F, Várkonyi G (2017) An annotated and illustrated checklist of Microgastrinae wasps (Hymenoptera, Braconidae) from the Canadian Arctic Archipelago and Greenland. ZooKeys 691: 49-101. https://doi.org/10.3897/zookeys.691.14491 - Fernández-Triana, Jose; Buffam, Joel; Beaudin, Melanie; Davis, Hannah; Fernández-Galliano, Ana; Griffin, Emily; Lin, Shang-Yao; McAulay, Megan K.; Richter, Robin; Rodriguez, Freddy; Várkonyi, Gergely (Zenodo, 2017)
Figure 10 - Dolichogenidea sp. 2. A Habitus, lateral B Metasoma, dorsal C Head, frontal D Fore wing E Head and mesosoma (partially), dorsal.